The Impact of Perceived Organizational Injustice on Employee Satisfaction, Organizational Commitment and Turnover Intention: A Study of Employees in MNCs in Malaysia - Chung, Kuok Shiong (2009)

(untitled)
The purpose of this research was to examine the impact of perceived organizational injustice on employees’ level of commitment and their intention to quit.